A criança surda e a escola bilíngue: discursividades sobre a infância surda - Job, Raquel Santos Pereira (2022)
This dissertation was produced under the line of research in Special Education, Inclusion and Difference of the Graduate Program in Education at the Federal University of Santa Maria. Provoked by the research problem - Is it possible to create the presence of a becoming-child in the context of early childhood education with regard to the discursive net about the deaf child in the education of the deaf? -, I sought to understand the discursive practices regarding early childhood education in schools of the deaf. In this atmosphere, I assume the Deaf Studies as a theoreticalmethodological reading grid, an area of study and educational research that has the deaf subject as its centrality, which encompasses linguistic, cultural and identity concepts. Inspired by Cultural Studies, I tried to understand how cultural practices circulate in the context of deaf people's lives, producing ways of being deaf in bilingual schools and their reverberations in the insertion of deaf children in this community. With decolonial studies, I find pedagogical possibilities for the insurgencies of events in early childhood education as a moment of creation and power to recognize in deaf childhood the becoming-child, creating other ways of being and living deaf childhood. Contributing to the conceptual framework of the research, the notions of discourse, power relations, government of childhood, experience and school were articulated, operated in this study under the post-structuralist perspective. As materiality, I find the discursive marks produced by normative documents: Resolution nº 5, of December 17, 2009, which establishes the Curriculum Guidelines for Early Childhood Education, and the document on Early Childhood Education in the National Common Curricular Base (BNCC), which deal with early childhood education in Brazil, as well as the discourses produced by the documents prepared by the deaf community: Ordinances nº 1.060/2013 and n/91/2013 of MEC/SECADI, the Report on the Linguistic Policy of Bilingual Education – Brazilian Sign Language and Portuguese Language and Teaching Libras as L1 in Early Childhood Education. Arriving at the bilingual school of the deaf floor and in its discursivities about deaf childhood, I work with school documents: Political-Pedagogical Project and School Regiment, as well as composing a class diary with narratives produced in this scenario, which I understand as practices of a speech that say something about the deaf child. I find in the speeches of teachers, parents, students and the child his/herself manifestations that say about the representations lived by the deaf child in the bilingual school space. Looking at the child in the deaf school made it possible to look at my teaching and the encounters that emerge in the day-to-day life of the school, as well as looking at the deaf childhood as the in-between place, which opens up possibilities for change and creation, a space for the singular, which does not categorize the deaf child only as a learner of a deaf identity.